Sistem Informasi Rumah Produksi 8Production Films Berbasis Web - Muhammad Rezki (APTIKOM SUMSEL, 2020)
Production House 8Production films is one of the production houses enganged in services that include multimedia, video shooting and photography in Palembang. The creation of this final project, entitled “Production House Information System In 8Production Films Based on Website”. Because currently the production process include visual shooting and shooting, visual image editing and photos are still not well scheduled, only initiative, and no scheduling systematically. In addition, the management of internal operational information in the processing data from the order receipt is only stored in the form of .doc files and some are still handwritten, so that the same data recording and processing (double storage), and acces to information is slow. The System development method used in this research is Prototype. Based on the problem that have been analyzed through exixting business process observation methods. Then the system is designed by making UML (Unifield Modeling Languange). And using PHP as a programming language that will be used to create the website PHP has the extension of PHP Hypertext Preprocessor, a programming language that is anabled to build a dynamic website. While MySQL is an RDBMS software (or database server) that can manage databases very quickly. Thw result of this study are a web-based 8Production Films Production House Information System that makes ordering users easy and makes it easier for 8Production films staff to perform member absences, managing filming schedules and weekly agendas to be more effective, and making monthly reports of transactions at web-based 8Production films production houses